2008
DOI: 10.1055/s-0028-1083634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Neoechinulin A and Derivatives

Abstract: Neoechinulin A isolated from Eurotium rubrum showed cytoprotection activity against peroxynitrite generated from SIN-1 [3-(4-morpholinyl)sydnonimine hydrochloride] in PC12 cells. As we are interested in this biological activity, we synthesized neoechinulin A and its derivatives. In this article, we fully report the isolation of natural neoechinulin A and B, a total synthesis of (-)-neoechinulin A, and determination of the absolute configuration of natural neoechinulin A. In addition, we describe herein synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…16. The synthesis of (-)-neoechinulin A by Kuramochi et al 41 A similar dehydration was described by Liu and coworkers in 2019. The dehydration of a functionalized -hydroxytryptophan 1.38 species was used to generate the corresponding dehydrotryptophan compound 1.39 as a key intermediate in the synthesis of speradine C (Scheme 1.17).…”
Section: Dehydrotryptophan Derivatives By Acid-catalyzed Elimination Of Water Fromhydroxytryptophanmentioning
confidence: 83%
See 3 more Smart Citations
“…16. The synthesis of (-)-neoechinulin A by Kuramochi et al 41 A similar dehydration was described by Liu and coworkers in 2019. The dehydration of a functionalized -hydroxytryptophan 1.38 species was used to generate the corresponding dehydrotryptophan compound 1.39 as a key intermediate in the synthesis of speradine C (Scheme 1.17).…”
Section: Dehydrotryptophan Derivatives By Acid-catalyzed Elimination Of Water Fromhydroxytryptophanmentioning
confidence: 83%
“…Janthinocin A can be dehydrated to give Janthinocin C under acidic conditions as demonstrated by Johnson et al 40 In 2008, Kuramochi and coworkers demonstrated that a -hydroxytryptophan dipeptide 1.35 could be used in the synthesis of Z-dehydrotryptophan-containing cyclic dipeptide neoechinulin A a potent antioxidant and radical scavenger. 41 They found that a diastereomeric mixture of a -hydroxytryptophan-containing dipeptide 1.35 could be converted to the corresponding Z-dehydrotryptophan-containing dipeptide upon exposure to acid 1.36 (Scheme 1.16). 41 The dehydration was found to take place more slowly than removal of the acid-labile indole protecting group.…”
Section: Dehydrotryptophan Derivatives By Acid-catalyzed Elimination Of Water Fromhydroxytryptophanmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, natural products serve as excellent sources for discovering antiviral agents. 1 We have previously reported that neoechinulin B ( 1a ), isolated from Eurotium rubrum Hiji025, 2 exhibited antiviral effects against hepatitis C virus (HCV). 3 Mechanistic studies revealed that this compound disrupted the formation of double-membrane vesicles (DMVs), which are the sites of viral RNA replication, by inhibiting the liver X receptor (LXR)-regulated gene induction required for DMV formation.…”
mentioning
confidence: 99%